PENDIDIKAN AGAMA ISLAM BAGI REMAJA KORBAN PENYALAHGUNAAN NAPZA (Narkotika, Alkohol, Psikotropika, dan Zat Adiktif) - rahimi, rahimi (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
Abstract The problem of drug abuse (narcotics, alcohol, psychotropic and addictive substances) has become an inseparable part and the problem of juvenile delinquency today. Blurring of Islamic values in the eyes of a teenagers one of the reasons is because they are exposed to a variety of contradictions and moral experience which causes them confused to choose which the best one for them. With religion, people can concern to the real purpose that is aimed to Rahmatan lil'alamin religion as a religion that came to identify his people to worship Allah primarily.